Pengaruh Profitability, Firm Size, Leverage Dan Tax Avoidance Terhadap Cash Holding Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei Tahun 2014-2018 - Herny Masytah Dewi; Wisnu Panggah Setiyono (Research Parks Publishing LLC, 2021)
This study aims to determine and analyze the effect Profitability, Firm Size, Leverage and Tax Avoidance on Cash Holding partially and simultaneously to find out the model that can be used to measure Cash Holding in companies by using panel data regression in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. This study applies quantitative method and the object of this research is done by population and sample randomly (purposive sampling), which are 21 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange on 2014-2018. The data use is taken from the secondary financial statement (annual report) company period 2014-2018. The technique analysis used panel data regression method with fixed effect model approach using Eviews 9. The results of this study showed that simultaneously variabels Profitability, Firm Size, Leverage and Tax Avoidance affect influence the Cash Holding. while partially Firm Size and Leverage have a significant effect on Cash Holding. Profitability and Tax Avoidance has no significantly influence on Cash Holding